THE POLICY OF ORGANIZATION, THE SPIRIT OF PROGRESSIVISM ISLAM, AND ITS ASSOCIATION WITH SOCIAL WELFARE EDUCATORS - Abdul Karim; Aiman Faiz; Nunuy Nur'Aini; Febiyana Yolanda Rahman (Balai Diklat Keagamaan Bandung, 2022)
The purpose of this article examines the advantages of understanding the spirit of progressive Islam, compliance with organizational policies related to social welfare. The research is carried out at SDIT Muhammadiyah Cirebon. The subjects of this study were the principal, 15 Educators, and 5 Education Personnel. This research uses qualitative which uses instruments in form of interviews, observations, and documentation, also strengthened quantitatively by questionnaires. The approach used is cultural interpretation. Descriptive statistical analysis is used to describe the general state, and the data obtained from the questionnaire will be analyzed statistically descriptively. The results showed that organizational policies are based on the spirit of progressive Islam, and the policy of SDIT Muhammadiyah’s principal through transforming, habituating, as well as forming values. Another finding is that the educators at SDIT Muhammadiyah are socially and financially prosperous. It can be concluded that education personnel have prospered socially in addition to compliance with the principal’s policies, also because the progressive Islam principles’ understanding.Keywords: Progressive Islam; Organizational Policy; Social Welfare; Muhammadiyah